Downregulation of microRNA-4324 promotes the EMT of esophageal squamous-cell carcinoma cells via upregulating FAK - Zhou, Jian (Onco Targets Ther, 2019)
Background: Esophageal squamous-cell carcinoma (ESCC) metastasis is the major cause of death of this severe and common malignancy. Focal adhesion kinase (FAK) is one of the key components of the focal adhesion complex, which is a multi-protein structure that controls cell adhesion, migration and invasion and regulates tumor metastasis. Purpose: To identify the roles and mechanisms of FAK in the regulation of Epithelial-to-mesenchymal transition (EMT) of ESCC cells. Methods: The expression of FAK and miR-4324 in both ESCC tissues and cells were evaluated by qRT-PCR and Immunohistochemistry analysis. Dual luciferase assays were performed for the confirmation of miR-4324’s specific binding to 3’UTR of FAK mRNA. Besides, the trans-well assays and wound healing assays were employed to evaluate the effects of FAK /miR-4324 axis on the EMT regulation of ESCC cells. Furthermore, the relationship between miR-4374/FAK expression and clinical pathologic parameters & patient survival were also statistically analyzed. Results: In this study, we identified the upregulation of FAK and downregulation of miR-4324 in both ESCC cells and tissues. Overexpression of miR-4324 mimic, which significantly decreased cellular FAK levels, can impair the invasion potential and migration ability of ESCC cells. Besides, co-transfection of FAK can attenuate the function of miR-4324 mimic. Further experimental results demonstrated that miR-4324 mimic remarkably downregulated epithelial-to-mesenchymal transition (EMT) phenotype, which can also be effectively prevented by overexpressing FAK in ESCC cells. What’s more, low miR-4324 and high FAK tissue levels have significant association with poor cell differentiation, tumor size and invasion depth as well as overall number of metastatic lymph nodes. Patients with high miR-4324 and low FAK levels in tumoral tissues lived longer than their counterparts, respectively. Conclusions: In conclusion, miR-4324/FAK axis could be a promising therapeutic target and potential prognostic biomarker for ESCC, which deserves further investigation in the clinic.